Case Report: Early-Onset Behavioral Variant Frontotemporal Dementia in Patient With Retrotransposed Full-Length Transcript of Matrin-3 Variant 5 - Castro, Madelyn; Venkateswaran, Nisha; Peters, Samuel T.; Deyle, David R.; Bower, Matthew; Koob, Michael D.; Boeve, Bradley F.; Vossel, Keith (Frontiers in Neurology, 2020)
Frontotemporal dementia (FTD) rarely occurs in individuals under the age of 30, and genetic causes of early-onset FTD are largely unknown. The current report follows a 27 year-old patient with no significant past medical history presenting with two years of progressive changes in behavior, rushed speech, verbal aggression, and social withdrawal. MRI and FDG-PET imaging of the brain revealed changes maximally in the frontal and temporal lobes, which along with the clinical features, are consistent with behavioral variant FTD. Next generation sequencing of a panel of 28 genes associated with dementia and amyotrophic lateral sclerosis (ALS) initially revealed a duplication of exon 15 in Matrin-3 (MATR3). Whole genome sequencing determined that this genetic anomaly was, in fact, a sequence corresponding with full-length MATR3 variant 5 inserted into chromosome 12, indicating retrotransposition from a messenger RNA intermediate. To our knowledge, this is a novel mutation of MATR3, as the majority of mutations in MATR3 linked to FTD-ALS are point mutations. Genomic DNA analysis revealed that this mutation is also present in one unaffected first-degree relative and one unaffected second-degree relative. This suggests that the mutation is either a benign variant or disease-causing mutation with incomplete penetrance, which has been observed in heritable FTD. Retrotransposons are not often implicated in neurodegenerative diseases; thus, it is crucial to clarify the potential role of this MATR3 variant 5 retrotransposition in early onset FTD.